Macular bruch membrane defects in highly myopic eyes: the Beijing Eye Study - You, Qisheng; Jonas, Jost B. (Retina, 2016)
Purpose: To examine prevalence and associations of macular Bruch membrane defects (MBMDs) in a population-based setting. Design: Population-based cross-sectional study. Methods: The Beijing Eye Study 2011 included 3,468 subjects who underwent a detailed ophthalmic examination including spectral domain optical coherence tomography with enhanced depth imaging of the macula. Macular Bruch membrane defects were defined as an interruption of Bruch membrane on the optical coherence tomography images in the macular region. Results: Macular Bruch membrane defects could be detected only in highly myopic eyes (defined as refractive error of ≤-6 diopters or axial length of ≥26.5 mm) with a prevalence of 17/164 (10.4%, 95% confidence interval [CI], 5.7%-18.1%). Best-corrected visual acuity <0.05 was found in 5 (29%) of 17 eyes with MBMDs, and in 7 (41%) eyes, visual acuity was <0.3 and ≥0.05. In the MBMD region, retinal pigment epithelium and choriocapillaris were completely lost, and the deep and middle layers of the retina and the choroid were almost completely absent. In the MBMD region, mean retinal thickness was 153 ± 57 μm (mean ± SD) and choroidal thickness was 12.7 ± 28.1 μm. On the fundus photographs, MBMDs appeared as whitish areas with round borders. In multivariate regression analysis, presence of MBMD was significantly associated only with longer axial length (Odds ratio: 3.87; 95% CI, 1.64-9.14). Conclusion: Macular Bruch membrane defects with a prevalence of approximately 10% in highly myopic eyes are associated with a complete loss of retinal pigment epithelium and choriocapillaris, an almost complete loss of photoreceptors and choroid, and marked reduction in visual acuity. Macular Bruch membrane defects may be added to the panoply of features of myopic maculopathy.
Gesehen am 28.03.2019